Product development and X-Ray microtomography of a traditional white pan bread from plasma functionalized flour. (15th January 2023) - Chaple, Sonal; Sarangapani, Chaitanya; Dickson, Shannon; Bourke, Paula
Abstract: Cold plasma (CP) technology has emerged as a novel non-thermal technology with the potential to improve food quality or impart functionality to ingredients. Our previous studies on wheat flour demonstrated how the structure and functionality of wheat flour might be modified using CP to provide an alternative to chemical additives (Chaple et al., 2020). However, understanding of the further effects of plasma functionalized ingredients in existing or new product formulation is limited. This study investigated the effects of CP treatment of wheat flour on traditional white pan bread development. The bread was formulated using plasma functionalized flour (PFF), and critical product characteristic responses were analyzed. Plasma treatment of flour positively affected the bread's expansion ratio, crust color, and water activity. Farinograph analysis suggests improvement in water absorption capacity, dough development time, and dough stability. X-Ray Microtomography (XRMT) analysis was conducted to understand how plasma functionalising the flour impacted the microstructure of bread. The 3D scans suggested no macro-change in the bread matrix compared to control; however, the porosity decreased in line with the increasing plasma treatment duration of the flour. The texture profile analysis showed an improvement in the gluten network developed in the dough developed from PFF. Sensory analysis results showed overall acceptance for bread formulated with PFF compared with a commercial sample. Overall, CP treatment of the flour improved the functionality in relation to dough and bread preparation and can thus provide an alternative to chemical additives in bread making. The CP processes may be modulated to deliver tailored effects for bread product development. Graphical abstract: Image 1 Highlights: The expansion ratio of bread improved using plasma functionalized flour. The porosity distribution ratio within the bread loaf increased with the flour treatment time. XRMT images indicated the increasing porosity distribution in bread with increasing flour treatment duration. Sensory analysis showed acceptance of bread developed from plasma functionalized flour using a consumer acceptance test.